Molecular analysis of human- and pig-derived Ascaris in Honduras. Issue 2 (5th March 2018) - Palma, A.; Ortiz, B.; Mendoza, L.; Matamoros, G.; Gabrie, J.A.; Sánchez, A.L.; Fontecha, G.
Abstract: Ascaris sp. is a soil-transmitted helminth (STH) significantly affecting the health of human and swine populations. Health inequities and poverty, with resulting deficiencies in water, sanitation and hygiene, are directly associated with Ascaris lumbricoides prevalence in humans. Resource constraints also lead to small-scale livestock production under unsanitary conditions. Free-ranging pigs, for instance, are exposed to a number of infectious agents, among which Ascaris suum is one of the most common. Under these conditions, close proximity between people and pigs can result in cross-contamination; that is, pigs harbouring human Ascaris and vice versa. Moreover, the potential interbreeding between these two Ascaris species has been demonstrated. The present study analysed Ascaris worms obtained from children and pigs in Honduras. Adult worms were collected from stool samples of children after pharmacological treatment, and from pigs' intestines after slaughter for commercial purposes at a local abattoir. A nuclear ribosomal internal transcribed spacer (ITS) region was amplified by polymerase chain reaction (PCR) and digested with a restriction enzyme in order to separate putative human- and pig-derived Ascaris isolates. PCR products were also sequenced, and cladograms were constructed. All parasites isolated from children showed the typical human-derived genotype of Ascaris, whereas 91% of parasites from pigs showed the expected pig-derived genotype. Cross-infections between hosts were not demonstrated in this study. Nine per cent of pig-derived worms showed a restriction band pattern highly suggestive of a hybrid human–pig Ascaris genotype. These results contribute to the understanding of ascariasis epidemiology and its zoonotic potential in a highly endemic region.